Penatalaksanaan Pemeriksaan Magnetic Resonance Imaging (MRI) Lumbal Dengan Kasus Hernia Nukleus Pulposus - Ameliya Widya Astuti; I Made Lana Prasetya; Tri Asih Budiarti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Magnetic Resonance Imaging (MRI) is the gold standard for diagnosing Hernia Nucleus Pulposus. Hernia of the Nucleus Pulposus (HNP) is a condition in which there is bulging of the nucleus pulposus. This study aims to determine the management of lumbar MRI examinations in cases of Nucleus Pulposus Hernia and the role of the Dixon sequence in cases of lumbar HNP. The Dixon sequence is an MRI method used for fat suppression and produces 4 contrasts in one scanning, including in phase, opposed phase, water and fat. The research method used is descriptive research with a case study approach. Data collection was carried out in January 2023 – February 2023 using a Philips 3 Tesla MRI aircraft. Subjects consisted of ten patients with clinical HNP. Data collection was carried out through observation, interviews and documentation. The research results were obtained according to theory using the sequence T1 SE/TSE sagittal, T2 SE/TSE axial, SE/TSE T1 axial, Short Inversion Recovery (STIR) while in the field using the sequence Survey, Myelo Radial, T2 Weighted Dixon Sagittal (T2 Fat Saturation Sagittal, T2 Sagittal), T1 Weighted TSE Sagittal, STIR TSE PSS Coronal, T1 Weighted TSE Axial, T2 Weighted TSE Axial.